2005
DOI: 10.1111/j.1365-2265.2005.02410.x
|View full text |Cite
|
Sign up to set email alerts
|

Congenital adrenal hyperplasia in adults: a review of medical, surgical and psychological issues

Abstract: SummaryOur knowledge of the experience of adults with congenital adrenal hyperplasia (CAH) as they pass through life is only now emerging. In this review we gather medical, surgical and psychological literature pertaining to adults with CAH and consider this alongside practical experience gained from a dedicated adult CAH clinic. There is increasing awareness for the need for multidisciplinary teams who have knowledge of CAH particularly with respect to gynaecological surgery and clinical psychology for women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
3
20

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 85 publications
1
80
3
20
Order By: Relevance
“…This has been attributed to several factors including psychological factors such as different gender behavior and low maternal interests; post-surgical difficulties with intercourse, anovulation, and menstrual irregularities; and the effect of progesterone hypersecretion on endometrial receptivity (2). The precise mechanisms underlying menstrual irregularities and anovulation remain uncertain, involving overproduction of androgen and/or progesterone (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…This has been attributed to several factors including psychological factors such as different gender behavior and low maternal interests; post-surgical difficulties with intercourse, anovulation, and menstrual irregularities; and the effect of progesterone hypersecretion on endometrial receptivity (2). The precise mechanisms underlying menstrual irregularities and anovulation remain uncertain, involving overproduction of androgen and/or progesterone (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Replacing steroid deficiency and avoiding the long-term consequences of CAH and glucocorticoid use are the aims of the current medical treatment. Studies have shown the presence of adverse outcomes in adult CAH patients (3,4). In a prospective cross-sectional study conducted in the United Kingdom in 203 patients, BMI was found to be higher than that in the health survey for England data, and osteopenia (40%) and osteoporosis (7%) were common (5).…”
Section: Introductionmentioning
confidence: 99%
“…This potentially explains the low rates of romantic partnerships and sexual activity reported in the investigations of women diagnosed with CAH [9, 11, 12, 17, 18]. Furthermore, for women who may want to get pregnant, problems with fertility (see [19] for a review of fertility research) may also impact willingness to pursue relationships, and some individuals have reported the inability to satisfy a potential mate's needs for children as a barrier to marriage (C. Migeon, personal communication, January 8, 2006).…”
Section: Health-related Quality Of Life Specific To Disorders Of Smentioning
confidence: 99%